Vaccination as an administrative social right - Aleksieva, Remina (Law Journal of New Bulgarian University, 2022)
Thе paper discusses the administrative social right to vaccination in the context of European and Bulgarian administrative law. It examines the interaction between the rights to privacy, freedom of religion and the right to health according to their content in the European Convention on Human Rights, the Constitution of the Republic of Bulgaria and current legislation. Also, the paper comments on the case law of the European Court of Human Rights (ECtHR) on these rights in relation to health hypotheses, aiming to strike a balance between the individual rights of citizens and social rights important for society as a whole. In the light of the case law and legal framework, the paper discusses the extent to which interference with the scope of these rights is regulated by law, pursues a legitimate aim and is necessary in a democratic society.